Pd/PTABS: An Efficient Catalytic System for the Aminocarbonylation of a Sugar-Protected Nucleoside - Bhilare, Shatrughn; Shah, Jagrut; Gaikwad, Vinayak; Gupta, Gaurav; Sanghvi, Yogesh S.; Bhanage, Bhalchandra M.; Kapdi, Anant R. (Synthesis, 2019)
A highly efficient and mild protocol for the aminocarbonylation of a nucleoside is developed by employing palladium/(1,3,5-triaza-7-phosphaadamantan-1-ium-1-yl)butane-1-sulfonate (Pd/PTABS) as the catalytic system. The developed aminocarbonylation methodology employs CO gas at a relatively low temperature of 60 °C and is suitable for a wide range of amines, including (heteroaryl)benzylic, aliphatic acyclic, alicyclic and secondary amines. This protocol is also utilized for the synthesis of a sangivamycin precursor by carrying out the Pd-catalyzed amination and aminocarbonylation simultaneously. The utility of this protocol is further demonstrated by the synthesis of the drugs moclobemide and nikethamide.
Keywords: palladium; PTABS; aminocarbonylation; nucleoside; sangivamycin